The Effect Of Blood Transfusion On The Risk Of Hepatitis B Infection In Hemodialysis Patients : Meta Analysis - Astuti, Yuli; Dewi, Yulia Lanti Retno; Murti, Bhisma (Jurnal Riset Kesehatan, 2025)
Background Hepatitis B is caused by infection with the Hepatitis B virus, this disease affects 240-280 million people in the world. Hepatitis B virus causes chronic disease that develops in liver damage, cirrhosis and liver cancer, more than 600,000 people die every year. Giving repeated blood transfusions increases a person's risk of developing hepatitis infection. Hemodialysis patients who receive blood transfusion therapy are more at risk of developing hepatitis infection. Objective of this study was to study and estimate the influence of blood transfusion history on the risk of hepatitis B infection in hemodialysis patients based on the results of previous similar studies by meta-analysis. Method is a meta-analysis conducted by searching for articles from the databased Google Scholar, PubMed, Springer Link, and Research Gate. The keywords used were "blood transfusion" OR "risk factor" AND "HBV" OR "hepatitis B infection" OR "TTI" AND "patient hemodyalysis" OR "Patient renal failure". The inclusion criteria in this study were full text articles, from 2000-2020, with a cross sectional study design. Article analysis using RevMan 5.3. Results of data analysis studies 6 articles in the forest plot, giving blood transfusions was able to increase the incidence of hepatitis B infection in hemodialysis patients 1.30 times more at risk than those who did not transfuse, statistically significant (aOR 1.30; 95% CI = 1.02-1.66; p = 0.03) and based on the funnel plot, there was no publication bias. Conclusion blood transfusion affects hepatitis B infection in hemodialysis patients.